Digging Our Own Graves Coal Miners and the Struggle over Black Lung Disease. - Smith, Barbara Ellen (Haymarket Books, 2020)
This fully updated edition of a classic work from one of the leading scholars of Appalachia documents a community's struggle against the deadly black lung disease.